The Effects of Gender Integration on Men: Evidence from the U.S. Military - Kyle Greenberg; Melanie Wasserman; E. Anna Weber (Institute of Labor Economics (IZA), 2024)
Do men negatively respond when women first enter an occupation? We answer this question by studying the end of one of the final explicit occupational barriers to women in the U.S.: in 2016, the U.S. military opened all positions to women, including historically male-only combat occupations. We exploit the staggered integration of women into combat units to estimate the causal effects of the introduction of female colleagues on men's job performance, behavior, and perceptions of workplace quality, using monthly administrative personnel records and rich survey responses. We find that integrating women into previously all-male units does not negatively affect men's performance or behavioral outcomes, including retention, promotions, demotions, separations for misconduct, criminal charges, and medical conditions. Most of our results are precise enough to rule out small, detrimental effects. However, there is a wedge between men's perceptions and performance. The integration of women causes a negative shift in male soldiers' perceptions of workplace quality, with the effects driven by units integrated with a woman in a position of authority. We discuss how these findings shed light on the roots of occupational segregation by gender.
Keywords: J16; H56; 330